UTILIZATION OF DISCORD APPLICATION AS AN ONLINE LEARNING MEDIUM IN SUBJECTS - Munawaroh, Nenden; Iswadi, Salma Mutia; Usman, Asep Tutun (Proceeding of International Conference on Islamic Education (ICIED), 2022)
This research was motivated by the closure of the Education unit due to Covid-19, which made students conduct online learning. This is the first time this has happened in Indonesia, so educators find it difficult to find the right and effective media in utilizing technology. Therefore, this study aims to utilize the Discord application media as an online learning medium. The research method using the R&D model method used by the researcher is the development of a 4-D model. The 4-D model consists of 4 stages: Define, Design, Develop and Disseminate. This research was conducted in class X SMAN 14 Garut involving 3 classes with a total of 75 students. Data was collected in this stunning of interviews, observations, validation sheets and s,studentudent learning outcomes ability tests. Based on the processed data, it was found that this Discord media is useful and feasible to be used as an online learning media and can increase the effectiveness of learning in students having an average score of 78 with good interpretation. Suggestions for further researchers must have a Discord Nitro accountto furtherr increase the effectiveness of learning in students.